1996
DOI: 10.1007/s005300050008
|View full text |Cite
|
Sign up to set email alerts
|

A synchronization algorithm for distributed multimedia environments

Abstract: Network synchronization plays a significant role in transmitting multimedia objects over computer networks. Even packets from a single channel must be synchronized due to the problems in a packet switching environment, such as network jitter, frequency, and time offsets. We present an algorithm that determines the set of packets generated periodically by various participants arriving at a node. The basic advantage of the proposed algorithm is that the receiver estimates the reference times (expected arrival ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Note that there is much research on the calculation, measurement, and estimation of the end-to-end delay, such as Escobar et al (1994), Ishibashi and Tasaka (1995), Ramanathan and Rangan (1993), Ravindran and Bansal (1993), Zarros et al (1996), and we will not discuss this further in this paper.…”
Section: Response Time Estimationmentioning
confidence: 97%
“…Note that there is much research on the calculation, measurement, and estimation of the end-to-end delay, such as Escobar et al (1994), Ishibashi and Tasaka (1995), Ramanathan and Rangan (1993), Ravindran and Bansal (1993), Zarros et al (1996), and we will not discuss this further in this paper.…”
Section: Response Time Estimationmentioning
confidence: 97%
“…Note that is the intramedia synchronization delay of the continuous media object. Thus, the playback deadline for an object can be met so long as its response time satisfies the relationship where , the end-to-end delay defined as the time from when the request for a particular object is issued to when the object can be played at the request site, is given by Research on the calculation, measurement, and estimation of the end-to-end delay can be found in [122], [129], [134], [157], and [158].…”
Section: E Synchronizationmentioning
confidence: 99%
“…In the literature, several mechanisms dealing with the problem of limiting delay jitter and/or skew in multimedia retrieval services have been presented [5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Many of these mechanisms can be classified into two categories: the first one comprises mechanisms based on the use of buffers at the destination site, the second on modification of retrieval times at the source site so as to compensate for delay jitter.…”
Section: Introductionmentioning
confidence: 99%